Modified robot-assisted nephroureterectomy with ureteral catheterization for radical resection of the distal ureter: Procedures and short-term outcomes - Hao Ji; Qikai Wu; Jianbo Ji; Yuhang Qian; Lingkai Cai; Kexin Bai; Qiang Cao; Xiao Yang; Yongke Cao; Qiang Lv; Pengchao Li (Heliyon, 2024)
Objectives: To describe a bladder cuff excision method modified with ureteral catheterization to better visualize the ureteral orifice during robot-assisted nephroureterectomy (RANU). Methods: We retrospectively analyzed 66 patients with upper urinary tract urothelial carcinoma of the renal pelvis and/or upper-mid ureter treated between January 2020 and January 2023. Among them, 32 patients (group A) underwent RANU supported by ureteral catheterization, and the remaining patients (group B) received routine transperitoneal RANU. Postoperative cystoscopy was performed routinely to compare the rates of residual ureteral orifice between the two groups. Results: Surgeries were completed uneventfully in all 66 patients, without blood transfusion or conversion to open procedures. The operative time, estimated blood loss, and postoperative length of hospital stay were similar between both groups. However, the mean time required for BCE in group A was shorter than that in group B (9.5 min vs. 16.0 min, p = 0.006). Cystoscopy at postoperative three months showed no ipsilateral ureteral orifice in group A, but residual ureteral orifice was found in 23.5% of patients in group B. During a short follow-up period of 16 months, no patients in group A experienced bladder tumor recurrence. However, two patients (5.9%) in group B developed bladder tumor recurrence, with one experiencing local tumor recurrence at the level of the ureteral stump. Conclusions: Our novel technique enables complete ureteral retrieval, accurate and rapid bladder cuff excision, which makes the procedure less invasive and safely reproducible during robot-assisted nephroureterectomy.